2018
DOI: 10.5604/01.3001.0012.5915
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of math achievement in the elementary school students grades 1-3

Abstract: Early math skills are a good predictor of later academic success. Finding what factors influence math performance might help educators create better and more efficient math programs. The goal of the present study was to assess the relationship of math achievement and verbal fluency, selective attention, visual-motor integration and inhibitory control. An additional goal was to assess the effect of gender and grade on math achievement. The sample for this study comprised 210 children from grades 1 to 3 (107 bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…In this research the gender differences in the math improvement were not found, meaning that girls and boys math abilities followed the similar trajectory. This finding is in line with other research in which there were no gender differences at an early school age (Memisevic, Biscevic, & Pasalic, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this research the gender differences in the math improvement were not found, meaning that girls and boys math abilities followed the similar trajectory. This finding is in line with other research in which there were no gender differences at an early school age (Memisevic, Biscevic, & Pasalic, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…A plethora of research indicated the strong link between working memory and math achievement (Alloway & Alloway, 2010;Ashcraft & Krause, 2007;Raghubar, Barnes, & Hecht, 2010). Other factors predicting math achievement include verbal fluency, selective attention, visual motor integration, and inhibitory control (Memisevic, Biscevic, & Pasalic, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was also hypothesized that the core executive functions measured with eFun and the EYT would predict school grades. The literature suggests that EFs positively associate with academic outcomes in school children (Bull and Scerif, 2001;St Clair-Thompson and Gathercole, 2006;Memisevic et al, 2018;Usai et al, 2018). In particular, working memory was expected to show the strongest positive correlation with academic outcomes (Bull and Scerif, 2001;St Clair-Thompson and Gathercole, 2006;Usai et al, 2018).…”
Section: The Current Study Evaluating Two New Child-friendly Executimentioning
confidence: 99%
“…Indeed, executive functions build a foundation for learning and academic success (Posner and Rothbart, 2007;Zelazo et al, 2016). Executive functions predict math, English and science achievements in school (Bull and Scerif, 2001;St Clair-Thompson and Gathercole, 2006;Memisevic et al, 2018;Usai et al, 2018). Research has shown that teachers value their students' EF capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid reasoning is viewed as a cornerstone of human cognition and can be defined as the capacity to think logically and solve problems in novel situations (Ferrer et al, 2009). Additional factors related to mathematical abilities include selective attention, semantic fluency, inhibitory control and visual-motor integration (Memisevic et al, 2018). Many of these skills belong to the construct of executive functions.…”
Section: Introductionmentioning
confidence: 99%